South Africa's Inclusion in BRICS: Challenges and Prospects for Development in Africa. Issue 2 (3rd July 2018) - Anuoluwapo, Durokifa; Abdul-Wasi, Moshood B.; Edwin, Ijeoma
Abstract: The forming of alliances on the international scene has reflected a provisional arrangement in the world economy. Amongst such alliances was the formation of BRICS by the five world economies—Brazil, Russia, India, China, and South Africa into what is commonly known as BRICS. BRICS is considered a joint initiative, aimed at shifting conventional norms in international economic and political cooperation to create a new trans-continental platform for these actors. Each member country in BRICS has, in one way or another, reflected growth either through its economy foreign policy, and developmental pursuit. However, South Africa is portrayed by some researchers as lagging behind, when compared to the other member countries. Hence, this study sought to analyse the potential mediumand long-term implications of South Africa's inclusion in BRICS. The study also aimed to underscore the benefits and risks associated with South Africa's membership in the alliance in the area of development; specifically poverty reduction, foreign policy, trade, and global partnership. The researchers collected secondary data to analytically critique the inclusion of South Africa in the BRICS alliance, its benefits, and shortcomings for development in South Africa, and in Africa as a whole. We argue that as a global player under BRICS, South Africa has opened a new vista of opportunities, including transnational gateways to Brazil, Russia, India, and China, with the attendant inflow of infrastructural and developmental investments, enriching educational exchanges and technology transfers. The article concludes by stressing the need for South Africa and other African countries to formulate policies that will drive meaningful development in their respective countries. The authors recommend that African leaders should come up with innate policies that are Africa-centred, that would incite development internally.